2018
DOI: 10.1155/2018/4193469
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soil Classification on Seismic Behavior of SMFs considering Soil‐Structure Interaction and Near‐Field Earthquakes

Abstract: Seismic response of a structure is affected by its dynamic properties and soil flexibility does not have an impact on it when the bottom soil of foundation is supposedly frigid, and the soil flexibility is also ignored. Hence, utilizing the results obtained through fixed-base buildings can lead to having an insecure design. Being close to the source of an earthquake production causes the majority of earthquake’s energy to reach the structure as a long-period pulse. Therefore, near-field earthquakes produce man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…With notable exception that of the 1985 Mexico earthquake [2], the effect of SSI to steel structures subjected to far-fault seismic motions seems to be marginal. So far, only a few parametric studies have been carried out on the investigation of the effect of SSI to steel structures [3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…With notable exception that of the 1985 Mexico earthquake [2], the effect of SSI to steel structures subjected to far-fault seismic motions seems to be marginal. So far, only a few parametric studies have been carried out on the investigation of the effect of SSI to steel structures [3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Shahbazi et al [55] studied the seismic behavior of special moment frames (SMFs) with special ductility undergoing near-and far-field earthquakes by considering different modes, including the effects of soil-structure interaction, permanent displacement (Fling step), and forward directivity in near-field earthquake records, as well as vertical component of near-field earthquakes. It was demonstrated that near-field earthquakes impose more damage on the structure than far-field earthquakes [56][57][58].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The live and live loads of 20 kN/m 2 and 65 kN/m 2 , respectively [36], were applied to all stories. But different loads were applied for roofs, at 54 kN/m 2 and 15 kN/m 2 , respectively [26,37]. All models were fulfilled based on the rigid bed which was used for all stories.…”
Section: Selected Numerical Modelsmentioning
confidence: 99%